1990
DOI: 10.3168/jds.s0022-0302(90)78684-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Selenium, Vitamin E, and Mammary Gland Health in Commercial Dairy Herds

Abstract: Nine well-managed dairy herds were monitored for 1 yr to determine if bulk tank SCC and rate of clinical mastitis were associated with dietary and plasma Se and vitamin E status. Intakes of Se and vitamin E were 1 to 16 mg/d and 100 to 900 mg/d, respectively. Plasma Se concentrations were correlated positively with intakes of Se below 5 mg/d but were independent of Se intakes above 5 mg/d. Feeding vitamin E increased plasma concentrations of tocopherol, but the influence of dietary vitamin E on plasma concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
2
23

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 19 publications
10
103
2
23
Order By: Relevance
“…Higher respiratory burst activity of neutrophils could lead to higher intracellular kill of bacteria. Our findings are in agreement with several authors who demonstrated that neutrophils from cows with supplemental Se (inorganic) increased intracellular kill of bacteria, enhanced viability and reduced extracellular hydrogen peroxide concentration as compared to non supplemented cows (Gyang et al, 1984;Grasso et al, 1990;Hogan et al, 1990). Malbe et al (2006) also demonstrated possible involvement of organic Se supplementation (4 mg/day) with Staphylococcus aureus inhibition in cow's whey.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Higher respiratory burst activity of neutrophils could lead to higher intracellular kill of bacteria. Our findings are in agreement with several authors who demonstrated that neutrophils from cows with supplemental Se (inorganic) increased intracellular kill of bacteria, enhanced viability and reduced extracellular hydrogen peroxide concentration as compared to non supplemented cows (Gyang et al, 1984;Grasso et al, 1990;Hogan et al, 1990). Malbe et al (2006) also demonstrated possible involvement of organic Se supplementation (4 mg/day) with Staphylococcus aureus inhibition in cow's whey.…”
Section: Discussionsupporting
confidence: 93%
“…Relatively high Se concentrations in the control group, even after withdrawal of Se supplementation before the experiment, might be responsible for lack of significant increases after supplementation. According to Weiss et al (1990), plasma Se concentrations were correlated positively with intakes of Se at a certain limit but were independent of Se intakes above the limit. Further, retention of absorbed Se is influenced both by animal status and the chemical form of Se administrated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…High serum Se concentrations were associated with reduced rates of mastitis and lower bulk-tank somatic cell counts [15].…”
Section: Introductionmentioning
confidence: 99%